Basic structures - Garrison, Philip, CEng.; Garrison, Philip, CEng. (Hoboken : Wiley-Blackwell, 2011)
'Basic Structures provides the student with a clear explanation of the structural concepts behind buildings, using many analogies and examples. In this new edition new chapters on design have been added, which serve as an introduction to the structural design process by describing (with no mathematics) the principles and structural processes on which structural design is based, and showing the range of designs that can be achieved with modern methods. In addition, the text has been updated generally and the concepts of deflection and buckling addressed more fully at appropriate points in the existing chapters. Real examples and case studies are used to ensure the concepts can be seen in use, and the book is well illustrated with full colour photographs and many line illustrations, giving the student a thorough grounding in the fundamentals and a'feel' for the way buildings behave structurally. With many worked examples and tutorial questions, the book serves as an ideal introduction to the subject'--
Machine generated contents note: Introduction -- Acknowledgements -- 1 What is structural engineering? -- 2 Learn the language: a simple explanation of terms used by structural engineers -- 3 How do structures (and parts of structures) behave? -- 4 Force, mass and weight -- 5 Loading - dead or alive -- 6 Equilibrium - a balanced approach -- 7 More about forces: resultants and components -- 8 Moments -- 9 Reactions -- 10 Different types of support - and what's a pin? -- 11 A few words about stability -- 12 Introduction to the analysis of pin-jointed frames -- 13 Method of resolution at joints -- 14 Method of sections -- 15 Graphical method -- 16 Shear force and bending moments -- 17 This thing called stress -- 18 Direct (and shear) stress -- 19 Bending stress -- 20 Combined bending and axial stress -- 21 Structural materials: concrete, steel, timber and masonry -- 22 More on materials -- 23 How far can I span? -- 24 Calculating those loads -- 25 An introduction to structural design -- 26 More on structural types and forms -- 27 An introduction to deflection -- Further reading -- Appendices -- Index.
Revision and expansion of: Basic structures for engineers and architects. 2005.
Includes bibliographical references and index.
Keywords: Structural engineering